Issues of Treatment and Use of Periods with Dependent Consequential Sentences in the Standard Albanian Language - Kurani, Aida; Muho, Anita (Mediterranean Journal of Social Sciences, 2012)
This paper is focused in the period with dependent consequential sentence in the Albanian (standard) language, as is hasbeen expressed in the second volume of the â€œGrammar of Albanian Languageâ€ (Syntax), publication of the Academy of Sciences ofAlbania, or in some other normative work. Considering it by the viewpoint of the language culture, we are of the opinion that someconstructions of foreign source must be left out of the syntactic norm or must get limited in their use, eg. â€œÃ‹shtÃ« shumÃ« e mirÃ«, pÃ«r tÃ«qenÃ« e vÃ«rtetÃ«â€, which seems to sound unnatural, or the subtype with the connection nÃ« mÃ«nyrÃ« qÃ« and predicate as a verb in theindicative mode. On the other hand, we are of the opinion that in the written discourse, especially in the publicity style or in the medialanguage in general (including movies' or documentaries' translations from foreign languages), must be used more intensively theconsequential periods faced more often in the popular language or in the spoken discourse, such as those with the dependent sentencebeing connected to the main one through the connection qÃ« with a commonly connected word or not. We think that this would not onlybring the written variation nearer to the spoken variation of the Albanian standard language, but it would also put one more stone in thewalls of the â€œcastleâ€ of the Albanian syntax language.